Penerapan Model Problem Based Learning untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa Ma Nurul Falah Kangge Pada Materi Persamaan Kuadrat - Amsidi, Mukmin (STKIP Muhammadiyah Kalabahi, 2025)
This study aims to describe the implementation of the Problem Based Learning (PBL) model in improving students' mathematical problem-solving abilities on quadratic equations material at MA Nurul Falah Kangge.The type of research is classroom action research (CAR) conducted in two cycles.Each cycle consists of planning, implementation, observation, and reflection.The instruments used include observation sheets, problem-solving ability tests, and documentation.The research results show an improvement in students' problem-solving abilities from cycle I to cycle II.The average problem-solving ability score increased from 50% in cycle 1 to 80% in cycle 2, and the percentage of students achieving the good category also increased to very good.Thus, the implementation of the PBL model has proven effective in improving students' mathematical problem-solving abilities.